The Preaching of the Village Clerics in Creating Religiosity in Youth - Rofik, Moh.; Sadili, Imam (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study examines the role of kyai kampung (village clerics) in fostering youth religiosity in Blumbungan Village, Pamekasan, Madura, where adolescents have previously engaged in negative behaviors such as illegal street racing, promiscuity, and hedonistic lifestyles influenced by Western culture. The study aims to explore how culturally grounded and participatory da’wah strategies shape youth religious awareness and behavior within the local social context. Using a qualitative interpretive approach with a case study design, data were collected through interviews, participant observation, and documentation from kyai, transformed adolescents, community leaders, and mosque administrators, selected via snowball sampling. Findings reveal that kyai kampung act not only as religious leaders but also as social companions, engaging youth in various religious activities such as pengajian, tajhizul mayit, and mosque programs, resulting in significant improvements in religious participation and moral conduct. The study concludes that culturally adapted, participatory da’wah effectively enhances youth religiosity and promotes social transformation in rural communities, providing a practical model for religious leaders and policymakers seeking contextually relevant approaches.